Fusion of cellulose binding domain from Trichoderma reesei CBHI to Cryptococcus sp. S-2 cellulase enhances its binding affinity and its cellulolytic activity to insoluble cellulosic substrates - Thongekkaew, Jantaporn; Ikeda, Hiroko; Masaki, Kazuo; Iefuji, Haruyuki (Enzyme and microbial technology, 2013)
► The CSCMCase and fusion enzymes were successfully expressed in Cryptococcus sp. S-2 (-ura5). ► The fusion enzymes were responsible for cellulose-binding capacity. ► The fusion enzymes displayed cellulolytic activity toward insoluble substrates. Cryptococcus sp. S-2 carboxymethyl cellulase (CSCMCase) is active in the acidic pH and lacks a binding domain. The absence of the binding domain makes the enzyme inefficient against insoluble cellulosic substrates. To enhance its binding affinity and its cellulolytic activity to insoluble cellulosic substrates, cellulose binding domain (CBD) of cellobiohydrolase I (CBHI) from Trichoderma reesei belonging to carbohydrate binding module (CBM) family 1 was fused at the C-terminus of CSCMCase. The constructed fusion enzymes (CSCMCase-CBD and CSCMCase-2CBD) were expressed in a newly recombinant expression system of Cryptococcus sp. S-2, purified to homogeneity, and then subject to detailed characterization. The recombinant fusion enzymes displayed optimal pH similar to those of the native enzyme. Compared with rCSCMCase, the recombinant fusion enzymes had acquired an increased binding affinity to insoluble cellulose and the cellulolytic activity toward insoluble cellulosic substrates (SIGMACELL® and Avicel) was higher than that of native enzyme, confirming the presence of CBDs improve the binding and the cellulolytic activity of CSCMCase on insoluble substrates. This attribute should make CSCMCase an attractive applicant for various application.